Answer:
Step-by-step explanation:
<u>Given functions:</u>
- f (x) = 2x + 2
- g (x) = 3x – 1
<u>To find:</u>
<u>Solution</u>
- (f/g)(x) = f(x)/g(x) = (2x + 2) / (3x - 1)
- (f/g)(2) = (2*2 + 2) / (3*2 - 1) = 6/5 = 1.2
Answer:
6??
Step-by-step explanation:
I <u>THINK</u> IT WOULD BE 6
19 can be equal to 19 and it should turn out to be as a whole number which is 1
ANSWER
Step 3
EXPLANATION
The given polynomial expression is:
![2 {p}^{2} - 3p - 7 - (3 {p}^{2} + p - 5)](https://tex.z-dn.net/?f=2%20%7Bp%7D%5E%7B2%7D%20%20-%203p%20-%207%20-%20%283%20%7Bp%7D%5E%7B2%7D%20%20%2B%20p%20-%205%29)
Fatau correctly expanded the parenthesis in the first step.
![2 {p}^{2} - 3p - 7 - 3 {p}^{2} - p + 5](https://tex.z-dn.net/?f=2%20%7Bp%7D%5E%7B2%7D%20%20-%203p%20-%207%20-%203%20%7Bp%7D%5E%7B2%7D%20%20%20-%20%20p%20%20%2B%20%205)
Fatau also correctly grouped the like terms to obtain:
![(2- 3) {p}^{2} + (- 3 - 1)p + (- 7 + 5)](https://tex.z-dn.net/?f=%282-%203%29%20%7Bp%7D%5E%7B2%7D%20%20%20%2B%20%28-%203%20-%201%29p%20%20%2B%20%28-%207%20%2B%20%205%29)
Fatau committed a mistake at the third step.
Instead of obtaining,
![- {p}^{2} - 4p - 2](https://tex.z-dn.net/?f=%20-%20%7Bp%7D%5E%7B2%7D%20-%204p%20%20%20-%202)
He mistakenly got:
![{p}^{2} - 2p +2](https://tex.z-dn.net/?f=%7Bp%7D%5E%7B2%7D%20%20%20%20-%202p%20%20%2B2)